Mapping Quantitative Trait Loci Associated With Graft (In)Compatibility in Apricot (Prunus armeniaca L.) - Pina, Ana; Irisarri, Patricia; Errea, Pilar; Zhebentyayeva, Tetyana (Frontiers in Plant Science, 2021)
Graft incompatibility between most popular Prunus rootstocks and apricot cultivars is one of the major problems for rootstock usage and improvement. Failure in producing long-leaving healthy grafts greatly affects the range of available Prunus rootstocks for apricot cultivation. In spite of recent advances related to the molecular mechanisms of a graft-union formation between rootstock and scion, information on genetic control of this trait in woody plants is essentially missing due to a lack of hybrid crosses, segregating for the trait. In this study, we have employed the next-generation sequencing (NGS) technology to generate the SNP markers and construct parental linkage maps for an apricot F1 population ‘Moniqui (Mo)’ × ‘Paviot (Pa)' segregating for ability to form successful grafts with universal Prunus rootstock ‘Marianna 2624’. To localize genomic regions associated with this trait, we genotyped 138 individuals from the ‘Mo × Pa’ cross and constructed medium-saturated genetic maps. The female ‘Mo’ and male ‘Pa’ maps were composed of 557 and 501 SNPs and organized in eight linkage groups that covered 780.2 and 690.4 cM of genetic distance, respectively. Parental maps were aligned to the P. persica v2.0 genome and revealed a high colinearity with the Prunus reference map. Two-year phenotypic data for characters associated with unsuccessful grafting such as necrotic line (NL), bar and wood discontinuities (BD and WD) and an overall estimate of graft-(in)-compatibility (GI) were collected for mapping QTLs on both parental maps. On the map of the graft-compatible parent ‘Pa’, two genomic regions on LG5 (44.9 - 60.8 cM) and LG8 (33.2 – 39. 2 cM) were associated with graft (in)-compatibility characters at different significance level depending on phenotypic dataset. Of these, the LG8 QTL interval was most consistent between the years and supported by two significant and two putative QTLs. To our best knowledge, this is the first report on quantitative trait loci (QTLs) for graft (in)-compatibility in woody plants. Results of this work will provide a valuable genomic resource for apricot breeding programs and facilitate future efforts focused on candidate genes discovery for graft (in)-compatibility in apricot and other Prunus species.